Morning Literacy Innovation Program Management: Silent Reading to Improve Concentration among Fifth Graders at SDN 1 Ngrandah - Fatma Elia Nur Sholekhah; Choirun Nisa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze how silent reading-based morning literacy programs are planned, implemented, evaluated, and focused on fostering concentration among fifth-grade students at SD Negeri 1 Ngrandah. This study departs from previous research, which has focused more on reading outcomes, while the management of morning literacy programs from an educational management perspective has been limited.Methodology: This study uses a descriptive qualitative approach. The research subjects consist of one principal, one fifth-grade teacher, and 21 fifth-grade students. Data collection techniques include observation, interviews, and documentation. Data validity is obtained through triangulation of sources and techniques, while data analysis is carried out using an interactive model that includes data reduction, data presentation, and conclusion drawing.Results: The results of the study indicate that structured, consistent silent reading-based literacy program management supported by reading corner facilities can create a calmer learning atmosphere, improve students' readiness and concentration before core learning, and foster independent reading habits. Most students showed an increase in learning readiness after the program was implemented.Applications/Originality/Value: This study offers a novelty in the aspect of managerial studies, namely by positioning silent reading not only as a reading strategy, but as a literacy program that is managed through management functions (planning, implementation, and evaluation) and its focus of application. These findings contribute theoretically to the development of school literacy program management and practically as a simple model that can be replicated by other elementary schools to foster student concentration and readiness to learn.